Trazando caminos. Extensión y políticas de inclusión educativa en escuelas secundarias - González, Rocío Alejandra; Maneglia, Rodrigo Eduardo; Carballo, Edgardo Esteban; Salvatierra, Lucas Emanuel; García Díaz, María Inés; Beiza Baez, Barbara Crhystal (Facultad de Periodismo y Comunicación Social, 2016)
The purpose of this work is to socialize the experience developed in a project of University Volunteers (hereinafter VU) which was directed  at stimulating the continuity of studies at the higher / university level (specifically during 2013-2015) begining the production and interpretation of different social discourses that promote discursive practices, especially related to academic discourse.